Effect of Cerium oxide nanoparticles derived from biosynthesis of Azadirachta indica on stability and performance of a research CI engine powered by Diesel-Lemongrass oil blends. Issue 4 (June 2023) - Ramalingam, Sathiyamoorthi; Sankaranarayanan, G; Senthil, S; Rohith, R.A; Santosh Kumar, R
The effects of performance and emission parameters of a mono-cylinder CI engine have been studied using new alternate fuel: Lemongrass oil (LGO) with nano additive (Cerium Oxide). The study focuses on a novel biosynthesis method (Plant-mediated synthesis) of CeO2 nano-additives from the Azadirachta indica plant, which is less toxic and more compatible with other chemical methods. The biosynthesis method is a simple, high-yielding, environmentally friendly alternative to chemical methods. Recently, a green technique based on impulsively decreasing elements such as polysaccharides, microorganisms (bacteria and fungas), or plant extract has been developed. This is due to the fact that the process is a simpler, non-hazardous, and environmentally friendly alternative technique when compared to the intricate chemical techniques of synthesis of nano-additives. The engine tests were carried out by using three different volumetric percentages (LGO25, LGO25 + 50 ppm and LGO25 + 100 ppm) and related with base diesel. The test outcomes revealed that the BSFC decreased by 4.98% and 6.83% and BTE increased by 1.76% and 2.27% at LGO25 + CE 50 ppm and 100 ppm concentrations, correspondingly. The CO emission decreased by 18.18% and 24.2%, HC emission decreased by 3.03% and 9.1%, NOx emission decreased by 14.8% and 31%, Smoke emission decreased by 10.5% and 15.1% for LGO25 + CE 50 ppm and 100 ppm correspondingly.